Understanding the Giant Enhancement of Exchange Interaction in Bi2Se3-EuS Heterostructures - Kim, Jeongwoo; Kim, Kyoung-Whan; Wang, Hui; Sinova, Jairo; Wu, Ruqian (Physical Review Letters, 2017)
A recent experiment indicated that a ferromagnetic EuS film in contact with a topological insulator Bi2Se3 might show a largely enhanced Curie temperature and perpendicular magnetic anisotropy [F. Katmis, Nature (London) 533, 513 (2016).NATUAS0028-083610.1038/nature17635]. Through systematic density functional calculations, we demonstrate that in addition to the factor that Bi2Se3 has a strong spin orbit coupling, the topological surface states are crucial to make these unusual behaviors robust as they hybridize with EuS states and extend rather far into the magnetic layers. The magnetic moments of Eu atoms are nevertheless not much enhanced, unlike what was reported in the experiment. Our results and model analyses provide useful insights for how these quantities are linked, and pave a way for the control of properties of magnetic films via contact with topological insulators.
CRIS-Team Scopus Importer:2023-03-27